New Trends in Argentine and Brazilian Cinema - Manzoni, Carla (Imagofagia, 2021)
Sobre Cacilda Rêgo y Carolina Rocha (Comps), New Trends in Argentine and Brazilian Cinema, Bristol-Chicago, Intellect books, 2011, 274 pp., ISBN 9781841503752. Palabras clave: reseña, Cacilda Rêgo, Carolina Rocha, New Trends in Argentine and Brazilian Cinema